2016
DOI: 10.1080/10720162.2016.1140602
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol on Self-Regulation of Sexual Arousal in Sexually Compulsive Men Who Have Sex with Men

Abstract: Individuals who meet criteria for sexual compulsivity tend to be more likely to engage in behaviors that may have negative consequences. Despite the clear public health relevance, however, little is known about the determinants of sexual compulsivity. This psychophysiological study examined self-regulation of sexual arousal in men high and low in sexual compulsivity, when sober and after alcohol consumption. A total of 43 men who have sex with men (MSM) participated and were presented with a series of erotic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Based on an IMM, we further hypothesize that while CSB will result in increased sexual activity/outlet and want for sexual activity, at the same time, it will likely lead to decreased sexual arousal and sexual satisfaction, due to the lag in liking. The literature provides some results consistent with this hypothesis (Janssen, Hoffmann, Goodrich, & Wilson, 2016; Laier, Pawlikowski, Pekal, Schulte, & Brand, 2013; Miner et al, 2015; Winters, Christoff, & Gorzalka, 2010), but more and more specific research on this topic is needed.…”
Section: Interconnectedness Of Sexual Self-regulation Factorsmentioning
confidence: 86%
“…Based on an IMM, we further hypothesize that while CSB will result in increased sexual activity/outlet and want for sexual activity, at the same time, it will likely lead to decreased sexual arousal and sexual satisfaction, due to the lag in liking. The literature provides some results consistent with this hypothesis (Janssen, Hoffmann, Goodrich, & Wilson, 2016; Laier, Pawlikowski, Pekal, Schulte, & Brand, 2013; Miner et al, 2015; Winters, Christoff, & Gorzalka, 2010), but more and more specific research on this topic is needed.…”
Section: Interconnectedness Of Sexual Self-regulation Factorsmentioning
confidence: 86%
“…Also, the 2 groups did not differ in subjective sexual arousal. An earlier study 56 found that the MSM who scored high on a sexual compulsivity scale responded less strongly to sexual stimuli than MSM who scored low on this scale. In addition, genital response levels were negatively correlated with erotica use.…”
Section: Discussionmentioning
confidence: 92%
“…Physiological data were recorded using a Limestone system (Limestone Technologies, Inc, Ontario, Canada). Erectile responses were operationalized as difference scores 56 and calculated by subtracting the average circumference recorded during the last minute of the prestimulus baseline period from the data obtained, and averaged at 10-second intervals, during the erotic film conditions. New penile gauges were used for each subject.…”
Section: Genital Responsesmentioning
confidence: 99%
“…Выявлена связь между КСП и признаками рискованного сексуального поведения (в том числе секс в состоянии опьянения и более высокая частота заражения ВИЧ и другими ИППП) [40,62,63]. Сексуально компульсивные мужчины менее успешно подавляют свои сексуальные реакции после потребления алкоголя [64]. КСП у МСМ связано с возникновением рискованных сексуальных решений и приемом психостимуляторов во время полового акта [39].…”
unclassified